Increasing customer retention through digital marketing and paramedic competency with hospital brand image as intervening variable / Mirza Ramadhany Erlinda and Alifah Ratnawati - Erlinda, Mirza Ramadhany; Ratnawati, Alifah (2022)
Customer retention is a way to retain customers in the business world. A well-maintained business relationship between the company and consumers will positively impact the company in converting customers into repeat buyers. One example of a business that is also a basic need for the community is health services. Therefore, the hospital is one of the important service facilities for the community. To survive and thrive, hospitals must always develop their quality of service and marketing strategies. Nowadays, digital marketing plays an important role in marketing because times have shifted to the digital era. This study analyses the hospital's brand image in increasing customer retention through digital marketing and paramedical competence at Sultan Agung Islamic Hospital Semarang and Islamic Dental and Oral Hospital of Sultan Agung Semarang. This research was an explanatory quantitative research, and data collection was done using questionnaires with a convenience sampling technique. The subjects in this study were dental and oral outpatients at Islamic Hospital of Sultan Agung Semarang and Islamic Dental and Oral Hospital of Sultan Agung Semarang, totalling 177 patients. Analysis of the data used in this study was conducted using Partial Least Square analysis. Based on data analysis, the researcher found that Paramedic Competency and Digital Marketing through Accessibility, Interactivity, and Informativeness increased Customer Retention with Hospital Brand Image as an intervening variable.